Optically tunable ultra-fast resistive switching in lead-free methyl-ammonium bismuth iodide perovskite films. Issue 12 (19th March 2021) - Poddar, Swapnadeep; Zhang, Yuting; Zhu, Yiyi; Zhang, Qianpeng; Fan, Zhiyong
Abstract : Optical switching with sub-threshold electrical stimulation was observed in lead-free methyl ammonium bismuth iodide perovskite films. The Re-RAM device also exhibited an ultra-fast electrical switching speed of 10 ns. Abstract : Resistive RAMs (Re-RAMs) have come to the fore as a rising star among the next generation non-volatile memories with fast operational speed, excellent endurance and prolonged data retention capabilities. Re-RAMs are being profusely used as storage and processing modules in neuromorphic hardware and high frequency switches in radio-frequency (RF) circuits. Owing to its intrinsic hysteresis and abundance of charge migration pathways, lead halide perovskites have emerged as a promising switching medium in Re-RAMs besides their ubiquitous usage in optoelectronic devices. Here, we adopted a lead-free eco-friendly methyl-ammonium bismuth iodide (MA3 Bi2 I9 ) perovskite (prepared by solvent-free engineering) as the switching medium sandwiched between copper (Cu) and indium doped tin oxide (ITO) electrodes. The devices exhibited a 10 4 high ON/OFF ratio that provided a large window for the multi-bit data storage in a single cell with good accuracy. Robust endurance of 1730 cycles and good data retention ability of >3 × 10 5 s were also observed. Careful switching speed measurements showed the devices can operate with an ultra-fast speed of 10 ns for writing and erasing respectively. The devices responded to light illumination and the prolonged retention of the opto-electrically tuned resistance states paved the way for image memorization.